Evaluation of skeletal muscle satellite cell activity in rodent models depicting muscle hypertrophy and atrophy - Sidique, Idris L. (2013)
Satellite cells are muscle-specific progenitor cells involved in the routine maintenance of skeletal muscle homeostasis, growth and regeneration. They are activated by various stimuli (myotrauma, growth factors etc), undergo rounds of proliferation as skeletal muscle myoblasts, to differentiate and fuse with each other to generate new myotubes or onto existing myofibres to augment growth or repair damaged fibres. Satellite cells contribute to hypertrophy by facilitating nuclear addition, which maintains contractile protein synthetic capacity. Conversely, during atrophy the dysregulation of satellite cells (e.g., via myogenic suppression), causes an opposing deficit in nuclear supplementation/contractile protein synthesis. The ‘activity status’ of satellite cells, an important determinant of muscle regenerative capacity is not routinely addressed in studies characterising mechanisms of muscle hypertrophy and atrophy. Therefore, the investigations described within this thesis examined the satellite cell specific signalling events that contribute to muscle loss or gain, in rodent models experiencing non-mechanically-induced muscle hypertrophy or atrophy.